2001
DOI: 10.1101/gad.870101
|View full text |Cite
|
Sign up to set email alerts
|

Tumor formation and inactivation of RIZ1, an Rb-binding member of a nuclear protein–methyltransferase superfamily

Abstract: The retinoblastoma protein-interacting zinc finger gene RIZ (PRDM2) is a member, by sequence homology, of a nuclear protein-methyltransferase (MTase) superfamily involved in chromatin-mediated gene expression. The gene produces two protein products, RIZ1 that contains a conserved MTase domain and RIZ2 that lacks the domain. RIZ1 gene expression is frequently silenced in human cancers, and the gene is also a common target of frameshift mutation in microsatellite-unstable cancers. We now report studies of mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
164
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(167 citation statements)
references
References 48 publications
3
164
0
Order By: Relevance
“…The RIZ gene produces two proteins, RIZ1 and RIZ2, because of the use of alternative promoters. Interestingly, only RIZ1 harbors a SET domain and appears to be the main target of inactivation in tumors (Huang 2002), and mice lacking Riz1 function only are prone to tumor formation (Steele-Perkins et al 2001). In accordance with a tumor-suppressive function of RIZ1, ectopic expression in cancer cell lines results in cell cycle arrest and/or apoptosis (He et al 1998;Jiang et al 1999).…”
Section: Setting Trithorax Imprintsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RIZ gene produces two proteins, RIZ1 and RIZ2, because of the use of alternative promoters. Interestingly, only RIZ1 harbors a SET domain and appears to be the main target of inactivation in tumors (Huang 2002), and mice lacking Riz1 function only are prone to tumor formation (Steele-Perkins et al 2001). In accordance with a tumor-suppressive function of RIZ1, ectopic expression in cancer cell lines results in cell cycle arrest and/or apoptosis (He et al 1998;Jiang et al 1999).…”
Section: Setting Trithorax Imprintsmentioning
confidence: 99%
“…RIZ1, originally isolated from its interaction with the RB tumor suppressor protein (Buyse et al 1995), was the first SET domain protein demonstrated to be a tumor suppressor (Steele-Perkins et al 2001). The RIZ1 SET domain was recently shown to be a histone H3 Lys 9-specific methyltransferase (Kim et al 2003).…”
Section: Setting Trithorax Imprintsmentioning
confidence: 99%
“…Both PRDM2 and PRDM1 have growth arrest and proapoptotic activities He et al, 1998). Deficiency in the PR-domain of PRDM2 causes tumor susceptibility in mice and mutations in this domain are present in human cancers (Steele-Perkins et al, 2001;. The MDS1-EVI1 (PRDM3) gene is commonly mutated in myeloid leukemia and also contains a PR domain (Fears et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups, including our laboratory, have investigated this marker on CLL B cells and found that greater than 30% CD38 expression within a CLL leukemic population correlates to an overall shorter time to progression and, in general, a poor clinical outcome. [1][2][3][4][5] However, another study suggests that scoring CLL B-cell CD38 expression using both percent-positive and mean fluorescence intensity (MFI) is a more accurate prognostic tool for B-CLL patients. 6 Recently, Ghia et al 7 found that even a small distinct population of CD38 pos cells, displayed as a small peak in a bimodal CD38-staining profile, was associated with progressive disease.…”
Section: Figurementioning
confidence: 99%
“…5 Indeed, haploinsuffuciency has been proposed as a model to explain the more aggressive phenotype of homozygous knockouts of RIZ, the most widely studied PRDM family member. 3 In addition, structural rearrangement, mutation and/or aberrant expression of RIZ, MDS-EVI1 and MEL1 have been reported in myeloid malignancies. 4,7,9 PRDM family members share the feature of expressing two protein products that differ in the presence or absence of the PR domain.…”
Section: Figurementioning
confidence: 99%